Analysis of the Influence of Corporate Image and Quality Perception on Customer Trust in Telecommunication Infrastructure Projects (Case Study at PT QDC Technologies) - Hendri Kustian; Edi Sugiono (Mandalika Journal of Business and Management Studies, 2025)
In business-to-business companies like PT. Qdc Technologies, customer satisfaction and trust are essential. This study aims to analyze perceptions of technical quality, functional quality, corporate image, customer satisfaction, and trust in facing competition in telecommunications infrastructure projects. The respondents are employees of companies that are clients of PT. Qdc Technologies. A total of 60 respondents directly involved in the collaboration were selected as the sample. Data was collected using questionnaires and analyzed descriptively, as well as through hypothesis testing based on Gronroos' theory, which evaluates the influence of perceptions of technical quality, functional quality, and corporate image on customer trust. The results show a positive assessment by respondents of the variables studied. However, hypothesis analysis indicates that corporate image significantly influences customer satisfaction. Similarly, perceptions of technical quality in telecommunications infrastructure projects are the dominant factor in customer trust. This study provides descriptive insights to improve PT. Qdc Technologies' weaknesses in project execution and evaluate the relevance of the applied theory to the type of business being conducted.